PROPHYLACTIC EFFECT OF HYDROALCOHOLIC EXTRACT OF COLOCASIA ESCULENTA LEAVES IN CFA AND FORMALDEHYDE INDUCED ARTHRITIC RATS - M., Kumbhar C.; Patil, S. Y.; Yadav, P. S.; Jadhav, P. H.; Metkari, V. B. (Asian Journal of Pharmaceutical Research and Development, 2014)
Adjuvant induced arthritis is a chronic crippling, skeleton muscular disorder having nearest approximation to human rheumatoid arthritis for which there is currently no medicine available effecting a permanent cure. Even modern drugs used for the amelioration of the symptoms, offer only temporary relief and also produce severe side effects. This work was aimed at the scientific validation of the ethno-pharmacological claim about Colocasia esculenta and its anti-arthritic property. In the present study, prophylactic antiarthritic activity of hydroalcoholic extract of Colocasia esculenta leaves is done by Complete Freund's adjuvant induced arthritis model and formaldehyde induced arthritis model. Paw volume, paw diameter and loss in body weight during arthritis condition were corrected on prophylactic treatment with hydroalcoholic extract of Colocasia esculenta leaves and Diclofenac. Serum parameters such as SGOT, SGPT and ALP were also estimated for assessing the anti- arthritic potential of hydroalcoholic extract of Colocasia esculenta leaves. The results of the current investigation concluded, hydroalcoholic extract of Colocasia esculenta leaves possess a significant anti-arthritic activity against Complete Freund's adjuvant induced arthritis and formaldehyde induced arthritis model and justifying its prophylactic role in arthritic condition. The observed antiarthritic activity may be due to the presence of phytoconstituents such as alkaloid and flavonoids.